Effect of Development of Systems and Mechanisms to Solve Problems of Teenage Pregnancy in Samut Sakhon Province - Punjapong, Sukhon (Journal of Preventive Medicine Association of Thailand, 2024)
Objective: This study aimed to study effect of developing systems and mechanisms for solving teenage pregnancy problems in Samut Sakhon Province. Methods: This research and development study was conducted between February and September 2024. The sample group consisted of 229 networks members and 241 teenagers under 20 years old. The research tools included a knowledge questionnaire, network participation assessment, perception of pregnancy risk, and pregnancy prevention behavior. Data were analyzed using descriptive statistics, Wilcoxon Signed Ranks Test and Paired t-test. Results: The Knowledge and behavior program to prevent teenage pregnancy consisted of the following components 1) knowledge about problems and effects of premature sexual intercourse, 2) knowledge and strengthening of preventive behavior related to teenage pregnancy, life skills and sexual education, 3) knowledge about reproductive health and family planning, 4) knowledge about sexually transmitted diseases (STDs) and HIV/AIDS, and 5) exchange of knowledge and evaluation. The results indicated that after the network development, there was statistically significant increase in overall knowledge scores (p<0.001), and statistically significant increase in overall participation (p=0.004). Adolescents demonstrate a significantly higher mean awareness of pregnancy risks (p<0.001). Access to information and health services overall increased significantly (p<0.001) and overall teenage pregnancy prevention behaviors also showed a significant increase (p<0.001). Conclusion: After organizing activities, knowledge and behavior programs to prevent teenage pregnancy. This causes behavior to prevent of teenage pregnancy to increase.